Programmable probiotic consortium employ an oleic acid-inducible system to sense and degrade cholesterol in high-fat diet mice - Qi Yang; Wei Xiang; Aman Khan; El-Sayed Salama; Sourabh Kulshreshtha; Jing Ji; Ying Wu; Xiangkai Li (Gut Microbes, 2025)
High cholesterol is a major risk factor for cardiovascular disease (CVD), and current treatment strategies primarily focus on inhibiting cholesterol synthesis and reducing cholesterol absorption. Engineered synthetic consortia are emerging as a promising alternative for lowering cholesterol level and improving cardiovascular health. In this study, Escherichia coli Nissle 1917 (EcN) was engineered to express three genes -IsmA, BSH, and BCoAT, individually. The IsmA-expressing strain achieved a 27.95% reduction in cholesterol, the BSH-expressing strain exhibited a bile salt hydrolase activity of 6.14 U/mL, and the butyric acid production of the BCoAT-expressing strain was 5.81 mmol/L. The synthetic consortium (IsmA-, BSH-, and BCoAT-expressing strains) reduced serum cholesterol level by 43.65% in mice fed high-fat diet. Further, an oleic acid-inducible system was incorporated into the synthetic consortium (GR-Syncon). In contrast to Syncon, GR-Syncon is capable of recognizing fatty acid levels and expressing target genes exclusively in high-fat environments. In high-fat diet mice, administration of GR-Syncon resulted in a 27.60% reduction in serum cholesterol, downregulated the expression of cholesterol synthase HMGCR (31.97%), and upregulated cholesterol hydroxylase Cyp7a1 (86.74%), optimizing lipid metabolism. GR-Syncon also down-regulated inflammatory cytokines (IL-1β, IL-10 and TNF-α), repair liver damage, improved intestinal permeability and maintained the stability of gut microbiota in high-fat diet mice. This study highlights the potential of engineered synthetic consortia as a sustainable and targeted strategy for managing cholesterol and treating CVD.